Dark, bright optical and other solitons with conformable space-time fractional second-order spatiotemporal dispersion - Bulut, Hasan; Sulaiman, Tukur Abdulkadir; Baskonus, Haci Mehmet (Elsevier Gmbh, 2018)
This paper constructs dark, bright, combined dark-bright, singular, combined singular soliton optical and singular periodic solutions to the conformable space-time fractional second order nonlinear Schrodinger equation with group velocity dispersion coefficient and spatiotemporal dispersion by using the extended sinh-Gordon equation expansion method. The constraint conditions for the existence of valid soliton solutions are given. The reported results in this study maybe helpful in explaining the physical meaning of the studied model. (C) 2018 Elsevier GmbH. All rights reserved.
Keywords: The extended ShGEEM; NLSE; STD; GVD; Conformable derivative; Optical solitons